Respuesta :

Answer:

[tex]f^{-1}[/tex](x) = [tex]\frac{x}{2}[/tex]

Step-by-step explanation:

let y = 2x

Rearrange making x the subject

divide both sides by 2

[tex]\frac{y}{2}[/tex] = x

changing y back into terms of x

[tex]f^{-1}[/tex](x) = [tex]\frac{x}{2}[/tex]

Answer:

f^-1(x) = x/2

Step-by-step explanation:

To find the inverse of a function, we exchange x and y and then solve for y

y =2x

Exchange x and y

x = 2y

and then solve for y

Divide by 2

x/2 =y

The inverse function

f^-1(x) = x/2